Ernst Friedrich Sieveking. Erster Präsident des Hanseatischen Oberlandesgerichts - Schröder, Hans Joachim (Mäzene für Wissenschaft, 2009)
Ernst Friedrich Sieveking is one of the outstanding personalities in Hamburg's history. He showed special talents at an early age, so that he was already a fully trained lawyer at the age of 21. He then joined a renowned law firm which he managed successfully for many years on his own. In 1879 Sieveking was appointed the first president of the newly founded Hanseatic Higher Regional Court in 1879. Until his death, for thirty years, he remained president of the Court of First Instance, which earned him a high reputation as an expert on maritime law. In addition, he was actively involved in the founding of Hamburg University, which is why he was also a member of the first board of trustees of the Hamburg Scientific Foundation. Surrounded by three representative buildings, the Sievekingplatz in Hamburg still reminds us of him to this day.